1978
DOI: 10.1177/00220345780570020401
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Toothbrushing with Different Concentrations of Chlorhexidine on the Development of Dental Plaque and Gingivitis

Abstract: This study showed that 0.15, 0.10, and 0.05% chlorhexidine gluconate solutions used on the toothbrush subsequent to scaling were for at least 45 days able to maintain plaque and gingivitis scores lower than those obtained 14 days after scaling and oral hygiene instruction. Discoloration of teeth and fillings were the only side effects observed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
10
0
1

Year Published

1979
1979
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 10 publications
3
10
0
1
Order By: Relevance
“…which showed that the addition of fiuoride to a chiorhexidine solution did not adversely affect its antiplaque action. The results of the present study also agree with those of previous workers who showed that a concentration of chjorhexidine as low as 0,05 per cent can be effective in helping to prevent piaque deposition (Bay 1978, Bonesvol! 1978 and gingival inflammation (Bay 1978, Luoma et al 1978).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…which showed that the addition of fiuoride to a chiorhexidine solution did not adversely affect its antiplaque action. The results of the present study also agree with those of previous workers who showed that a concentration of chjorhexidine as low as 0,05 per cent can be effective in helping to prevent piaque deposition (Bay 1978, Bonesvol! 1978 and gingival inflammation (Bay 1978, Luoma et al 1978).…”
Section: Discussionsupporting
confidence: 92%
“…The results of the present study also agree with those of previous workers who showed that a concentration of chjorhexidine as low as 0,05 per cent can be effective in helping to prevent piaque deposition (Bay 1978, Bonesvol! 1978 and gingival inflammation (Bay 1978, Luoma et al 1978). In the present study, as in previous studies (Bay 1978, Bonesvoli 1978, Luoma et al 1978, plaque was not completely inhibited, nor was gingival infiammation completely prevented.…”
Section: Discussionsupporting
confidence: 92%
“…Indeed, many studies have demonstrated that 0.1 % and 0.12 % CLX mouthrinse have a significant comparable effect on plaque reduction as 0.2 % CLX formulation (9-12). …”
Section: Introductionmentioning
confidence: 99%
“…6 A lower concentration of CHX (0.12%) has been tested in animals and human populations and has also demonstrated clinical benefits. 7,13,14 Although CHX is an effective antimicrobial agent in both concentrations, comparison of the two existing formulations is still necessary. The aim of the present study was to assess the efficacy of two concentrations of chlorhexidine solutions (0.12% and 0.20%) on plaque development and gingival bleeding control during 14 days.…”
mentioning
confidence: 99%